Body composition before and after six weeks preseason training in professional football players - Egan, E.; Reilly, T.; Chantler, P.; Lawlor, J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Following 6 weeks preseason training, percent body fat measurements, as measured by DEXA, were reduced in all players, a significant (P<0.001) mean change of 2.0% body fat. Actual body fat values were reduced by 2.0 kg. Whole body bone mineral density values showed a significant increase over the preseason training period (p<0.01). Increases in lean mass were not significant (P>0.1). Body fat estimates for DEXA and skinfold methods were highly correlated (r=0.89, p<0.001).